2016
DOI: 10.3389/fpls.2016.01723
|View full text |Cite
|
Sign up to set email alerts
|

A Wheat Cinnamyl Alcohol Dehydrogenase TaCAD12 Contributes to Host Resistance to the Sharp Eyespot Disease

Abstract: Sharp eyespot, caused mainly by the necrotrophic fungus Rhizoctonia cerealis, is a destructive disease in hexaploid wheat (Triticum aestivum L.). In Arabidopsis, certain cinnamyl alcohol dehydrogenases (CADs) have been implicated in monolignol biosynthesis and in defense response to bacterial pathogen infection. However, little is known about CADs in wheat defense responses to necrotrophic or soil-borne pathogens. In this study, we isolate a wheat CAD gene TaCAD12 in response to R. cerealis infection through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
1
36
0
1
Order By: Relevance
“…In conclusion, CAD genes play significant role in various metabolic pathways such as lignification, pathogen defense, growth, and abiotic and biotic stress mechanism [39]. Consequently, the results presented here support to understand CAD genes functions in various biological processes in plants and to contribute to in silico and experimental studies about CADs involvement to these processes.…”
Section: The Gene Structure and Phylogenetic Analysis Of Plant Cadssupporting
confidence: 69%
“…In conclusion, CAD genes play significant role in various metabolic pathways such as lignification, pathogen defense, growth, and abiotic and biotic stress mechanism [39]. Consequently, the results presented here support to understand CAD genes functions in various biological processes in plants and to contribute to in silico and experimental studies about CADs involvement to these processes.…”
Section: The Gene Structure and Phylogenetic Analysis Of Plant Cadssupporting
confidence: 69%
“…Although PbCAD3 belongs to the bona fide CAD clade, its expression level was much weaker in fruits than in buds. Therefore, PbCAD3 may not be responsible for lignin biosynthesis in fruit, or it may be induced under specific circumstances such as insect attack or other damage ( Rong et al, 2016 ). Similar expression levels were found for PbCAD7 and - 9 in fruit, and the trends of PbCAD1 , - 19 and - 25 expression were not significantly correlated with lignin and stone cell contents.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, molecular breeding is important to uncover the mechanism of wheat defense against R. cerealis and to identify new resistance regulators from the wheat genome. Previous studies in Zhang’s laboratory have identified several genes that are involved in wheat defense response against R. cerealis , such as TaPIE1 ( Zhu et al, 2014 ), TaAGC1 ( Zhu et al, 2015 ), TaCAD12 ( Rong et al, 2016 ), and TaRCR1 ( Zhu et al, 2017 ). However, no study about the role of PP2A in wheat defense responses to pathogens has been reported yet.…”
Section: Introductionmentioning
confidence: 99%